PENGARUH PEMELIHARAAN DAN OPERASIONAL TERHADAP KINERJA GARBARATA DI BANDAR UDARA INTERNASIONAL RADIN INTEN II LAMPUNG - Delia Ratna Sari; Anton Budiarto; Yuyun Suprapto (Prosiding SNITP (Seminar Nasional Inovasi Teknologi Penerbangan))
Passenger comfort is important for the management of Radin Inten II Lampung International Airport. Scheduled equipment maintenance is necessary to maintain airport operational performance, as well as to maximize the maintenance and operational performance of the aviobridge and to improve service to passengers and airlines that use the aviobridge service. At this time the operation of the aviobridge with the maintenance intensity that has been applied, there are still obstacles to the aviobridge but it does not cause the aviobridge not to operate. The service for using the aviobridge at Radin Inten II Airport Lampung is very good and on time, but it is necessary to evaluate the prevention of repairs once a year in order to prevent damage and replace items on the aviobridge that have problems and work abnormally. The maintenance and operation of the aviobridge has an influence on the performance of the aviobridge, therefore this is investigated as a material to determine how much maintenance is carried out to better maintain the performance of the aviobridge to improve the quality of service to users of the aviobridge service.